Gaps in obesity management in the UAE and the role of bariatric endoscopy - Maryam Alkhatry (Frontiers in Gastroenterology, 2023)
The definitions of overweight and obesity include increased fat storage that might compromise one’s health. According to the World Health Organization (WHO), an adult is considered overweight if their Body Mass Index (BMI) is greater than or equal to 25, and obese if their BMI is greater than or equal to 30. Age must be taken into account when defining overweight and obesity in children. The prevalence of obesity and overweight was reported to be at 21% and 33%, respectively, in the Middle East region. As obesity incidence rises with ageing, those over 40 were found to have the highest prevalence of obesity and overweight. According to the Central Intelligence Agency’s World Factbook, the UAE has a prevalence rate of obesity of 31.7%, making it one of the top 20 nations in the world for high obesity rates in 2016. The prevalence of overweight and obesity in the UAE is estimated to have increased between 1989 and 2017 threefold.